1973
DOI: 10.1128/aac.3.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines and Host-Defense Mechanisms

Abstract: The effects of different tetracyclines on the bactericidal action of serum and on phagocytosis and intracellular killing of bacteria were investigated. Opsonization, phagocytosis, and intracellular killing were not significantly affected by any of the investigated tetracyclines. The bactericidal action of serum on Escherichia coli was substantially reduced by all tetracyclines investigated. In this respect, doxycycline had a much more pronounced action than the other tetracyclines. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

1981
1981
1987
1987

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…Previous reports on the effects of tetra cyclines on the phagocytic activity of human PMN have presented evidence for either a depressive effect [2,4,6,7,13,15] or no influence [8,9]. Under certain circum stances a depressive effect was found also in the present system.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous reports on the effects of tetra cyclines on the phagocytic activity of human PMN have presented evidence for either a depressive effect [2,4,6,7,13,15] or no influence [8,9]. Under certain circum stances a depressive effect was found also in the present system.…”
Section: Discussionsupporting
confidence: 65%
“…Over the years evidence has been produced indicating that this anti biotic may influence the host defence mech anisms [3-7, 13, 15]. Previous reports on the interaction between tetracyclines and the phagocytic system have presented evi dence for a depressive effect [2,4,6,7,13, 15J or no effect [8,9], Besides the report of Adam et al [1] we have not been able to find any investigation indicating that tetracy clines enhance the phagocytic activity of hu man leukocytes. As our primary studies seem to yield similar results, further investi gations were undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of the interaction of antibiotics and the immune system have involved predominantly phagocytic and microbicidal function (6,7,13,19,35). Lehrer (19), for example, found that the sulfonamides interfered with the normal activities of human polymorphonuclear leukocytes, an effect which appeared to be involved with the myeloperoxidase-mediated pathway, and Welch et al (35) showed reduced polymorphonuclear leukocyte activity in the presence of tetracycline and trimethoprim.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in fluorescence intensity occurred when 4 (4,7,8,12,14). In our study, high concentrations of doxycycline reduced PMNL random migration, CL, and glucose oxidation, whereas minocycline had a marked effect on CL and glucose oxidation.…”
mentioning
confidence: 70%
“…However, in another study, Forsgren and Gnarpe have failed to demonstrate any effect on these functions (7). Oxytetracycline has been reported not to inhibit PMNL functions (7). We have previously shown that doxycycline does not reduce in vivo PMNL migration to skin chambers (10) and have indicated that the impairment of PMNL functions measured in vitro may be due to photo-induced production of toxic oxygen species or due to the divalent cation chelating effect of tetracyclines or both.…”
mentioning
confidence: 99%